2014
DOI: 10.1161/strokeaha.114.005724
|View full text |Cite
|
Sign up to set email alerts
|

Different Risk Factor Profiles for Ischemic and Hemorrhagic Stroke in Type 1 Diabetes Mellitus

Abstract: W orldwide, cerebrovascular disease is the second leading cause of death not only in high-income but also in lowincome countries. Patients with type 1 diabetes mellitus have a markedly increased risk of stroke compared with nondiabetic subjects, 1 and it is of note that these patients are at a high risk of stroke 10 to 15 years earlier than nondiabetic subjects. 2 Age, hypertension, atrial fibrillation, smoking, and diabetes mellitus are well-known risk factors for stroke in the general population. [2][3][4][5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 31 publications
(27 reference statements)
6
42
0
2
Order By: Relevance
“…Moreover, after we subgrouped stroke (there were much fewer hemorrhagic strokes in all patient groups), the hazard ratio for hemorrhagic stroke was increased in the type 1 diabetes patients, although the total numbers were too few to make any firm interpretations of that observation. Some studies have shown an association between hyperglycemia and hemorrhagic stroke,38 and other studies have not 33. Our finding is consistent with other reports demonstrating a weak or even a lack of association between HbA1c levels and stroke in diabetes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, after we subgrouped stroke (there were much fewer hemorrhagic strokes in all patient groups), the hazard ratio for hemorrhagic stroke was increased in the type 1 diabetes patients, although the total numbers were too few to make any firm interpretations of that observation. Some studies have shown an association between hyperglycemia and hemorrhagic stroke,38 and other studies have not 33. Our finding is consistent with other reports demonstrating a weak or even a lack of association between HbA1c levels and stroke in diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…In diabetes, hypertension has a stronger association with stroke than hyperglycemia has 30, 31, 32. Nevertheless, the association between hyperglycemia and increased risk of stroke has been demonstrated in some,33 but not all studies2 in diabetes individuals. Long‐term studies in type 2 diabetes individuals comparing intensive versus standard glycemic control treatment have all failed to demonstrate a reduced risk of death and CVD (including fatal or nonfatal stroke) 34, 35, 36.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]16,17 However, none of the previous studies has specifically examined the association between glycated hemoglobin and stroke risk in diabetic patients with atrial fibrillation. Glycated hemoglobin was also found to be associated with increased risk of ischemic stroke in non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…We are unable to provide any plausible explanations for this observation, but a study of patients with type 1 diabetes mellitus (patients with early debut of diabetes mellitus and, therefore, with longer duration of their disease in this study) found duration of diabetes mellitus to be a risk predictor for ischemic stroke, but not hemorrhagic stroke. 37 Considering some limitations of the present bleeding analysis (few bleeding events in the longer duration category, and use of claimed prescriptions and not actual verified usage of vitamin K antagonists to identify treatment periods, making it impossible to evaluate the impact of noncompliance), further studies investigating this matter are needed. However, these results suggest that when considering commencement of anticoagulant treatment, special emphasis may be directed toward patients with longer duration of diabetes mellitus.…”
Section: Interpretation and Clinical Perspectivementioning
confidence: 99%